2016
DOI: 10.1016/j.whi.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Position of Authority, and the Risk of Depression and Posttraumatic Stress Disorder among a National Sample of U.S. Reserve Component Personnel

Abstract: BACKGROUND Recent United States military operations in Iraq and Afghanistan have seen dramatic increases in the proportion of women serving, and the breadth of their occupational roles. General population studies suggest that women, compared to men, and persons with lower, as compared to higher, social position may be at greater risk of post-traumatic stress disorder (PTSD) and depression. However, these relations remain unclear in military populations. Accordingly, we aimed to estimate the effects of (1) gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…However, to our knowledge, this is the first study to assess direct and indirect effects of gender on depression among a cardiac population, with a particular focus on PTSD as a mediator. Previous studies have found that women are at higher risk of comorbid PTSD and depression symptoms compared to men [53, 54], similar to our findings which showed a direct significant association of female gender with PTSD and a significant indirect effect of gender on depression mediated by PTSD. Reasons for these gender differences could be attributed to the different types of traumatic or stressful situations which men and women are exposed to, different responses to trauma, and different symptom-related responses, all of which may affect the course and severity of symptoms [55].…”
Section: Discussionsupporting
confidence: 91%
“…However, to our knowledge, this is the first study to assess direct and indirect effects of gender on depression among a cardiac population, with a particular focus on PTSD as a mediator. Previous studies have found that women are at higher risk of comorbid PTSD and depression symptoms compared to men [53, 54], similar to our findings which showed a direct significant association of female gender with PTSD and a significant indirect effect of gender on depression mediated by PTSD. Reasons for these gender differences could be attributed to the different types of traumatic or stressful situations which men and women are exposed to, different responses to trauma, and different symptom-related responses, all of which may affect the course and severity of symptoms [55].…”
Section: Discussionsupporting
confidence: 91%
“…This finding adds to a growing body of research concerning gender-associated health outcome differences in military populations and highlights the need for additional gender-focused research [64]. To that end, an interesting avenue for future research might lie in more deeply documenting the factors, such as social support from fellow unit members, that may be lacking in the post-deployment environment for female servicemembers.…”
Section: Discussionmentioning
confidence: 76%
“…In particular, the number of women veterans increased from 2% of troops stationed in Vietnam war to 10% in OEF/OIF (Murdoch et al, 2006), and it is known there are differences in the number of trauma between male and female veterans (Cohen et al, 2016). Thus, it will be worth examining how or if the combat exposure differently influences veterans depending on gender.…”
Section: Discussionmentioning
confidence: 99%